Ethnic Chinese Social Assimilation in Cibadak Chinatown Bandung - Rizaldi, Dzakwan (Universitas Pendidikan Indonesia, 2018)
This research is motivated by the existence of Ethnic Chinese as one of the minority groups in Indonesia. This study aims to get an overview of the Ethnic Chinese social assimilation in the Chinatown of Cibadak, Bandung. The research was a Qualitative Approach with Case Study Method with data collection techniques through documentation study, field observations, interviews and literature studies. The results of this study indicate that (1) The arrival of Ethnics Chinese coming to the city of Bandung is motivated by economic motives for seeking fortune in the city of Bandung. (2) The process of social assimilation of ethnic Chinese in Cibadak Chinatown is still ongoing, the process of intermingling occurs because of social interaction factors as well as cultural factors that are driven by the political policies of the government. (3) The manifestation of Chinese ethnic social assimilation in Cibadak Chinatown can be seen through the Sundanese language skills possessed by the ethnic Chinese, members of the barongsai community, which are mostly Sundanese, food (noodles and Bacang) that do not contain pork, marriages with Sundanese ethnicity until conversion religion. The problem faced by the current process of social assimilation by the Chinese Ethnic is experiencing a setback in the younger generation due to lack of communication and social contact with other ethnicities in Cibadak Chinatown. The social assimilation of the ethnic Chinese still occurs and can be felt by us, despite the decline, but the ethnic Chinese as one of the ethnic descendants in Indonesia still maintain the value of their ancestors.